Canadian after-school care providers' perceived role promoting healthy lifestyles: a focused ethnography - Pierrette H. Elias; Genevieve Montemurro; Lauren Sulz; Brian Torrance; Kate E. Storey (BMC, 2020)
Abstract Background After-school care programs have garnered interest in recent years as the hours of 3:00-6:00 p.m. are an opportune time for children to engage in healthy behaviours, specifically healthy eating and physical activity. Care providers are major influencers within the after-school care setting, impacting health promoting opportunities for children. However, little is known regarding the role care providers play in health promotion interventions in the after-school care setting, specifically those using comprehensive approaches. The purpose of this research was to explore care providers' role and experience promoting healthy eating and physical activity through the after-school care health promotion intervention School's Out ... Let's Move (SOLMo). SOLMo was guided by the evidence-based comprehensive school health framework. SOLMo had two main goals: [1] to serve a healthy snack with vegetable or fruit, and milk or water as the drink; [2] to include 30 min of moderate to vigorous physical activity. The intervention included resources and coaching for care providers to promote healthy eating and physical activity for children and took place in four after-school sites over a six-month period. Three of four sites were located in a school. The primary researcher was engaged with the sites over 22-months. Methods This research was guided by the qualitative method focused ethnography. Semi-structured interviews with care providers (n = 13) taking part in SOLMo were conducted. Participant observation was included as part of data generation to further understand care provider roles. Latent content analysis was utilized iteratively and concurrently throughout data generation. Results Overall, care providers were supportive of promoting health behaviours in the after-school setting. Through analysis, five themes and eight subthemes emerged related to care providers' role and experience promoting healthy eating and physical activity through SOLMo: 1) enhanced awareness; 2) improved programming; 3) strong relationships; 4) collaborative approach; and 5) role tension. Conclusions As major influencers, care providers play a crucial role in promoting healthy lifestyle behaviours for children. This research provides valuable insight into this role and the implementation of comprehensive health promotion approaches in the after-school setting. Findings contribute to the implementation knowledge base and help inform the promotion of healthy lifestyle behaviours for children.